Strategi Pembentukan Karakter dalam Perspektif Imam al-Haddad - Abdul Haris Rifai; M. Fahrudin Ghozali; Moh. Nurhakim (Ar-Raniry: International Journal of Islamic Studies, 2021)
This study proposed to understand the strategy of character building from the perspective of Imam al-Haddad. This study used a qualitative approach with the type of library research. The research data were collected using documentation techniques and analyzed using content analysis. The results showed that the strategy of character building according to Imam al-Haddad can be classified into two parts, namely: First, character building through spiritual improvement, which includes strengthening belief and faith in Allah SWT, improving intention before committing an act, fostering an introspective attitude, hold fast to the Qur'an and al-Sunnah, cleanse the mind of despicable traits, carry out religious obligations, and do sunnah deeds and their manners. Second, character building through good habits, which include managing and filling time with positive activities, cleaning the body, practicing daily etiquette according to the teachings of the prophet Muhammad SAW, being wira'i, speaking well, getting along with good people, love for Allah, amar ma'ruf nahi munkar, being fair, easy to forgive, devoted to parents, establish friendship, and respect and imitate teachers. The strategy of character building according to Imam al-Haddad's perspective strengthens the theory of strategy of character building according to Imam al-Ghazali's perspective.